2016
DOI: 10.1371/journal.pone.0165300
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Environment Dependent Modulation of Staphylococcus aureus Branched-Chain to Straight-Chain Fatty Acid Ratio and Incorporation of Unsaturated Fatty Acids

Abstract: The fatty acid composition of membrane glycerolipids is a major determinant of Staphylococcus aureus membrane biophysical properties that impacts key factors in cell physiology including susceptibility to membrane active antimicrobials, pathogenesis, and response to environmental stress. The fatty acids of S. aureus are considered to be a mixture of branched-chain fatty acids (BCFAs), which increase membrane fluidity, and straight-chain fatty acids (SCFAs) that decrease it. The balance of BCFAs and SCFAs in US… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
134
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(145 citation statements)
references
References 74 publications
11
134
0
Order By: Relevance
“…In S. aureus, BCFAs comprise 44 to 63% of the membrane and a BCFA-deficient strain exhibits reduced adherence to host cells and is attenuated in vivo (107, 145, 146). …”
Section: Bcaas At the Crossroads Of Metabolism And Virulencementioning
confidence: 99%
“…In S. aureus, BCFAs comprise 44 to 63% of the membrane and a BCFA-deficient strain exhibits reduced adherence to host cells and is attenuated in vivo (107, 145, 146). …”
Section: Bcaas At the Crossroads Of Metabolism And Virulencementioning
confidence: 99%
“…A paper in 2011 [11] reported that the 2-position is exclusively occupied by 15:0 fatty acids even in presence of millimolar concentrations of 18:1, while a paper in 2016 [77] reported that branched-chain fatty acids were reduced to less than 40% of the total cellular acyl chain composition so 16:0 and 18:1 is assumed to make up at least 10% of the 2-position composition. The difference between these two papers is what was measured and how it was measured.…”
Section: Pathways For Exogenous Fatty Acid Incorporationmentioning
confidence: 99%
“…It was found that all phosphatidylglycerol species contained 15:0 fatty acids. In contrast, Sen and coworkers [77] performed gas chromatography analysis on fatty acid methyl esters generated from hydrolyzing the total lipid extracts. Because lipid extracts contain non-phospholipid components like staphyloxanthin and media components such as free fatty acids and lipoproteins adsorbed to the bacterial cell surface, this form of analysis is less accurate at measuring phospholipid acyl chain composition.…”
Section: Pathways For Exogenous Fatty Acid Incorporationmentioning
confidence: 99%
“…Notably this was due to a reduced proportion of anteiso-branched chain fatty acids, as the proportion of iso-branched chains remained similar between the strains (Fig 1B). Overall, the fatty acid composition of these strains closely matched those of other S. aureus strains cultured in Müller-Hinton broth [26].…”
Section: Resultsmentioning
confidence: 82%